MORPHOLOGY OF THE CURRENT ISLAMIC COLLEGE OUTFIT (Semiotic Study on the Shift of Student Clothing Standards at UIN Sunan Ampel Surabaya) - Achmad Zaidun; Moh Atikurrahman (IAIN Manado, 2023)
Abstract: This study discussed the fashion phenomenon, especially the variety and shifts in contemporary fashion among students in Islamic university. Using semiotics to discuss students’ dress code in Islamic university is a rare perspective. Most studies focus more on discussing fashion codes and their implementation, and dress codes are not discussed as the main material object of research, or clothing is not understood as something that has a system within itself. As a result, the discourse regarding clothing as a system of cultural markers becomes murky. This study examined Muslim students' clothing using Saussurean semiotics in terms of a structured sign system. For Saussure, a sign consists of the relationship between signifier and signified. The first element is material and concrete. Meanwhile, the second element is mental and abstract. Apart from these elements, a sign is built from the relationship between langue as social conventions and parole as individual expressions. Meanwhile, clothing is a non-verbal semiotic element that has multi-articulation through the smallest meaningful elements called morphemes and the smallest elements that are meaningless but function to differentiate meaning called phonemes. In the context of UIN Sunan Ampel as a cultural locus of our study, the clothing practices of students from the oldest PTKIN campus in East Java were fragmented into two, namely santri and non-santri fashion. This event illustrated the dynamics of fashion on a campus that was found on Islamic values and principles.Keywords: Fashion, dress code, students, semiotics, Saussurean.Abstrak: Artikel ini membahas fenomena fesyen mahasiswa, khususnya ragam dan pergeseran busana kiwari di kalangan civitas akademica perguruan tinggi Islam di Indonesia. Meskipun penelitian tentang dresscode mahasiswa dari kampus-kampus Islam telah jamak dilakukan, namun studi semiotika seputar busana mahasiswa muslim masih sangat jarang dilakukan. Sebagian besar hasil penelitian yang tersedia lebih berfokus pada diskusi kode etik busana dan penerapannya. Praktis dresscode tidak dikaji sebagai pakaian itu sendiri. Imbasnya wacana terkait pakaian sebagai sistem penanda kultural menjadi sumir. Studi ini meneliti pakaian sebagai fokus diskusi dengan pendekatan semiotika Barthesian. Bagi Roland Barthes sebuah pakaian memiliki tiga lapis struktur, meliputi; pakaian itu sendiri, ikon tentang pakaian, dan narasi tentang pakaian. Alibinya, dari sepotong busana seseorang sejatinya tengah menyatakan sesuatu melalui suatu modus penstrukturan yang rigid. Pakaian merupakan elemen semiotik nonverbal yang memiliki artikulasi ganda melalui elemen-elemen terkecil bermakna yang disebut morfem dan elemen-elemen terkecil yang tak-bermakna namun berfungsi untuk membedakan makna yang disebut fonem. Dalam konteks UIN Sunan Ampel Surabaya sebagai sebuah lokus kultural, praktik berbusana di kalangan mahasiswa terfragmentasi menjadi dua, yakni fesyen santri dan nonsantri. Peristiwa ini menggambarkan dinamika fesyen pada sebuah kampus yang dirintis dari nilai dan prinsip Islam.Kata Kunci: Fesyen, dress code, mahasiswa, semiotika, Saussurean